2020
DOI: 10.1183/23120541.00486-2020
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Propionibacterium acnes in granulomas associates with a chronic disease course in Dutch sarcoidosis patients

Abstract: BackgroundSeveral studies demonstrated that Propionibacterium acnes (P. acnes) may be involved in sarcoidosis pathogenesis. Presence of P. acnes was found in granulomas of the majority of Japanese sarcoidosis patients. However, presence of P. acnes in tissue has never been related to sarcoidosis phenotypes and clinical outcome. Therefore, the aims of our study were to demonstrate whether P. acnes can be detected in granulomas of Dutch sarcoidosis patients and to investigate whether its presence is related to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 25 publications
(27 reference statements)
0
21
0
Order By: Relevance
“…Interestingly, a major increase in SAA expression in human monocytes and macrophages was found after a combined treatment with lipopolysaccharide (LPS) and dexamethasone or methylprednisolone [ 20 ]. In a previous study, we showed the presence of C. acnes lipoteichoic acid (LTA) in granulomas of sarcoidosis patients [ 15 ]. Comparable to LPS of gram-negative bacteria, LTA is a cell wall polymer of gram-positive bacteria and plays a role in bacterial growth, membrane homeostasis, and virulence [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a major increase in SAA expression in human monocytes and macrophages was found after a combined treatment with lipopolysaccharide (LPS) and dexamethasone or methylprednisolone [ 20 ]. In a previous study, we showed the presence of C. acnes lipoteichoic acid (LTA) in granulomas of sarcoidosis patients [ 15 ]. Comparable to LPS of gram-negative bacteria, LTA is a cell wall polymer of gram-positive bacteria and plays a role in bacterial growth, membrane homeostasis, and virulence [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work we identified trigger-related phenotypes in sarcoidosis based on immunological sensitization for mycobacterial antigens and presence of Cutibacterial antigens in granulomas [ 14 , 15 ]. Based on its function as an acute phase protein upregulated by infections and contribution in bacterial clearance [ 1 , 16 , 17 ], together with its considered role as a biomarker in sarcoidosis, increased SAA levels may reflect underlying microbial antigens or autoantigens as triggers in a subgroup of sarcoidosis patients.…”
Section: Introductionmentioning
confidence: 99%
“…Formalin-fixed, paraffin-embedded tissue sections were immunohistochemically stained with the PAB antibody, a C. acnes -specific monoclonal antibody that binds to the cell membrane-bound lipoteichoic acid (LTA) of the bacterium [ 5 ]. Full methods are described elsewhere [ 6 ]. Differences in the presence of C. acnes between the patient groups was compared using the Chi-squared test.…”
mentioning
confidence: 99%
“…a) Characteristics of all included patients and percentage of patients with presence of C. acnes in tissue or in tissue and granulomas. The sarcoidosis group was previously described [ 6 ]. No significant difference was observed between the three groups regarding C. acnes in tissue or C. acnes in granulomas (p=0.210 and p=0.460, respectively).…”
mentioning
confidence: 99%
See 1 more Smart Citation